The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/toxins10110477
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Quantitative Risk Assessment of Twelve Mycotoxins in Eggs and Chicken Tissues in China

Abstract: Aflatoxins (AFs), deoxynivalenols (DONs), and zearalenones (ZENs) are common mycotoxins that contaminate feedstuff, causing contamination of poultry products. In our study, these mycotoxins were quantified in 152 egg samples collected from markets in Jiangsu (JS), Zhejiang (ZJ), and Shanghai (SH) and in 70 chicken tissue samples (liver, heart, and gizzard) from ZJ in China. The main mycotoxins observed in egg samples were DON, 15-AcDON, and ZEN, although only ZEN family mycotoxins (ZEN, α-ZEL, β-ZEL, and α-ZAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Dry food is mostly a basis of pet diet and even extremely low doses of mycotoxins might result in chronic diseases when consumed daily. Mycotoxins could be ingested by the animal with contaminated food and accumulate in their tissues or excrete with body fluid, hence, meat, milk, and eggs might be also potentially an origin of mycotoxins in diet [42][43][44][45]. It might be concluded that multi-exposure to mycotoxins is an inevitable phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Dry food is mostly a basis of pet diet and even extremely low doses of mycotoxins might result in chronic diseases when consumed daily. Mycotoxins could be ingested by the animal with contaminated food and accumulate in their tissues or excrete with body fluid, hence, meat, milk, and eggs might be also potentially an origin of mycotoxins in diet [42][43][44][45]. It might be concluded that multi-exposure to mycotoxins is an inevitable phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that in field conditions non-specific signs of mycotoxicosis associated with the presence of multiple contributing factors occur, making it difficult to establish a clinical diagnosis. OTA has the potential to bioaccumulate in the organism, and thus consumption of OTA by birds may also be associated with the appearance of OTA residues in edible tissues and eggs [ 7 , 8 ], which might affect the safety of egg production throughout the food chain. Among food commodities, little is known about the risks posed by exposure to mycotoxins by consuming poultry products in Serbia [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that OTA-induced toxicity can activate apoptosis, in the nephrons of the kidneys [11]. Exposure of poultry to OTA is responsible for avian ochratoxicosis [12]; however, the sensitivity of different birds species to OTA is variable. In addition, the role of OTA in nephrotoxicity remains elusive.…”
Section: Introductionmentioning
confidence: 99%